Monkeypox: Concern about an emerging zoonosis - Vega-Fernández, Jorge Arturo (2022)
background: Monkeypox is a viral zoonotic disease caused by the poxvirus of the same name, endemic to central and western Africa. However, its presence has increased in other regions of the world during the last decade compared to the previous 40 years. Objective. To describe and update the etiologic, epidemiologic, and clinical features of simian pox, as well as to discuss the potential risk of international spread. Material and Methods. A review of literature published in the last five years was performed using the descriptors Medical Subject Headings. The search was performed in the MEDLINE/PubMed and LILACS databases, without language restrictions. Duplicate studies and those that did not fit the research objective were excluded, selecting 47 articles. Results. Simian smallpox virus is related to human smallpox virus (eradicated in 1979). It is transmitted from a sick individual by respiratory fluid droplets, contact with skin lesion material and body fluids; or by contaminated fomites. After 6 to 13 days of incubation, symptoms appear, similar to those of human smallpox: beginning with an acute febrile process and followed by a cutaneous eruption on the face and body, which heals leaving visible scars. Conclusions. This virus may occupy the ecological niche left by the smallpox virus. It has now spread to Europe and America, so it should no longer be considered a disease limited to Africa, but a health threat to global public health.